2021
DOI: 10.1590/0037-8682-0835-2020
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of Maytenus guianensis (Celastraceae) against Aedes aegypti (Diptera: Culicidae)

Abstract: INTRODUCTION: Bioprospection of plant products is used to discover new insecticides. METHODS: The larvicidal activity of ethanolic extract and triterpene (tingenone B) from the bark of Maytenus guianensis and their effect on pupation and emergence were evaluated against Aedes aegypti . RESULTS: Crude extract LC 50 was 11.3 ppm and caused ejection of the larvae in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Despite the insecticidal potential of several plant species, according to Vieira et al [16], the toxic mechanisms of action of their bioactive compounds on organisms need to be better understood. These secondary metabolites exert significant larvicidal effects on insects by ingestion or contact [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the insecticidal potential of several plant species, according to Vieira et al [16], the toxic mechanisms of action of their bioactive compounds on organisms need to be better understood. These secondary metabolites exert significant larvicidal effects on insects by ingestion or contact [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts deriving from Celastraceae plant parts have been used as insect repellents and insecticides in traditional agriculture in South America and China (Deepa & Narmatha Bai, 2010). Several sesquiterpenes stand out among bioactive compounds found in this family of plants, since they have the potential to be used for the aforementioned purposes (Avilla et al, 2000;Deepa & Narmatha Bai, 2010;Li et al, 1997;Martins et al, 2021;Spivey et al, 2002). e fact that A. populnea belongs to the Celastraceae group explains the interest in pharmacological studies focused on investigating its crude or isolated and identified bioactive extracts.…”
Section: Introductionmentioning
confidence: 99%